Acquired Immunodeficiency Syndrome: A Review - Lenka, Rajesh Kumar; Das, Chandan (International Journal of Psychosocial Rehabilitation, 2019)
HIV stands for the virus that causes HIV, a human immunodeficiency virus. "HIV" may be used to identify the virus or HIV infection. AIDS is the inherited condition of immunodeficiency. AIDS is the current level of infection with HIV. The CD4 infection control cells of the immune system are attacked and destroyed by HIV. CD4 cell loss makes treating diseases and certain cancers impossible for the human body. HIV will phase out the immune system and move towards AIDS without treatment. These 13 treatment and care protocols form the cornerstone of the strategic actions of WHO in its contribution to the universal access of the United Nations Member States to HIV / AIDS prevention, treatment and support services. These replace HIV / AIDS Treatment and Care: CIS (2004) WHO guidelines and have been adapted explicitly to the whole WHO of Europe. The 13 guidelines together provide a comprehensive and evidence based method to provide clear and specific instructions for the diagnosis and management of a wide range of HIV / AIDS-related health problems, such as antiretroviral treatment, for adults, young people and infants. Treatment of opportunistic infections, influenza, hepatitis, injection drug use, sexual and reproductive health, mother-to-child transmission of HIV, vaccination, palliative care and prophylaxis after exposure. Since treatment and care for people living with HIV is an ever developing field, these protocols can be updated in the future.